2023
DOI: 10.1002/adma.202205709
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Deposition Profiles Influence Foreign Body Responses

Abstract: Fibrosis remains a significant cause of failure in implanted biomedical devices and early absorption of proteins on implant surfaces has been shown to be a key instigating factor. However, lipids can also regulate immune activity and their presence may also contribute to biomaterial‐induced foreign body responses (FBR) and fibrosis. Here it is demonstrated that the surface presentation of lipids on implant affects FBR by influencing reactions of immune cells to materials as well as their resultant inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
(75 reference statements)
2
9
0
Order By: Relevance
“…[ 28 ] A recent study by Schreib et al., reported that lipids were deposited by host cells on the surface of a biomaterial after implantation and that the types of lipids correlate with how the immune system reacts to the biomaterial. [ 9 ] The anti‐inflammatory implants demonstrated significant enrichment of phospholipids hypothesized to be anti‐fibrotic at the explanted implant surface. Our observation of glycerolipids in the tissue above the anti‐fibrotic M1‐inducing samples in our study suggests that these two observations may be linked.…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ] A recent study by Schreib et al., reported that lipids were deposited by host cells on the surface of a biomaterial after implantation and that the types of lipids correlate with how the immune system reacts to the biomaterial. [ 9 ] The anti‐inflammatory implants demonstrated significant enrichment of phospholipids hypothesized to be anti‐fibrotic at the explanted implant surface. Our observation of glycerolipids in the tissue above the anti‐fibrotic M1‐inducing samples in our study suggests that these two observations may be linked.…”
Section: Resultsmentioning
confidence: 99%
“…Implantation of materials or devices triggers the FBR first occur at the implantation site include blood-material interactions, provisional matrix formation, acute inflammation, chronic inflammation, granulation tissue development, and fibrous capsule development. [26][27][28] There are many similarities between FBR and normal wound healing. During normal wound healing, a series of well-orchestrated and overlapping phases were included: inflammation, cell proliferation, matrix deposition, and lastly tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…With the help of rotavap using silica under optimized pressure, the filtrate was dried. Using 120 g ISCO silica column liquid chromatography by dichloromethane: ultra (22% MeOH in dichloromethane (DCM) with 3% NH 4 OH) mixture 0% to 40% for purification and then characterized by nuclear magnetic resonance (NMR) mass spectroscopy and electrospray ionization mass spectrometry (ESI-MS) [12,17]. NMR was performed using Bruker AVANCE III HD 600 MHz.…”
Section: Synthesis Of Rza15mentioning
confidence: 99%
“…Vegas et al discovered a triazole containing a small molecule (RZA15) through a combinatorial screening approach that [10] leads to reduction of the recruitment and attachment of the macrophages [11]. This was confirmed using intravital imaging in vivo, was instrumental in establishing the hypothesis that this novel class of small molecules can be used as an immunomodulatory agent to coat the NPs, helping in reduced immune recognition, macrophage uptake, and improved blood circulation and targeting to diseased site [12,13].…”
Section: Introductionmentioning
confidence: 99%